Determination of the Geoid–Quasigeoid Separation Using GGI Method - Marek Trojanowicz; Magdalena Owczarek-Wesołowska; Yan Ming Wang (Remote Sensing, 2024)
The determination of the geoid–quasigeoid separation (GQS) is most often based on the use of Bouguer gravity anomalies or disturbances with additional corrections, which allow for the determination of so-called complete or accurate GQS values. This study presents analyses related to an attempt to determine accurate GQS values using the GGI approach (based on the geophysical gravity inversion technique). This approach allows for the modeling of various parameters of the gravity field, and it also enables the determination of the GQS or geoid undulations. Such capabilities of the method have not yet been tested. In this study, the details of the GGI solution in terms of determining the GQS and the first results from tests performed in the area of the Colorado 1 cm geoid computation experiment are presented. The GQS values determined by the GGI approach were compared with the reference values determined previously using the complete classical approach. The differences between the compared values were small, with a standard deviation of 0.007 m, and the maximum differences reached 0.075 m. The analyses also revealed the significant impact of changes in the density of topographic masses on both the geoid undulations and GQS values determined using the GGI approach.